SISTEM INFORMASI PEMESANAN JASA LAYANAN INTERNET BERBASIS WEB PADA PT. FIRMAN HOTSPOT MEDIATAMA MENGGUNAKAN FRAMEWORK - Pratama, Gelard Untirtha; Ashidiqi, Hasbi; Safaatulloh, Asep; Arief, Rahadian (LPPM Universitas Bina Bangsa, 2024)
This study aims to develop an information system for ordering web-based internet services at PT. Word Hotspot Mediatama. This information system is designed to increase customer efficiency and convenience in submitting and ordering internet networks. The system analysis method used is SWOT to identify customer needs and the ordering process. Furthermore, system design is carried out using the SDLC method with the Waterfall type to describe the workflow and relationships between the entities involved. In the growing digital era, internet access has become a basic need. Therefore, it is important for internet service providers to provide an efficient and effective information system to manage internet network installation orders. This research presents an innovative solution, namely the development of a Web-Based Internet Service Ordering Information System at PT. Word Hotspot Mediatama. At the implementation stage, this system allows customers to place orders online through the PT. Word Hotspot Mediatama. Customers can fill out the application form and complete personal data and choose the desired internet network package. After the data is verified, the customer will receive a notification in the form of an installation schedule and payment instructions. Customers can also monitor the installation process via their order page. The implementation of this system uses the powerful Laravel Framework, ensuring data security and optimal performance. Through the integration of web technologies, customers can quickly check service availability, submit installation requests, and monitor the progress of their orders. This information system provides multiple benefits, facilitating customers in ordering internet services and enabling PT. Firman Hotspot Mediatama to improve operational efficiency. Thus, this research makes a positive contribution in improving the quality of service in the internet network installation industry